Hubungan Tingkat Stres Dengan Kejadian Nyeri Dismenorea Pada Mahasiswa Kebidanan Akademi Kebidanan Bandung - Fauzul Munah; Zulfa Nur Azizah; Shinny Ria Pratiwi (Pelantar Press, 2025)
Background: Adolescent Menstruation is an early process that indicates that a female adolescent has experienced puberty. Dysmenorrhea can affect women who menstruate at any age. Almost 90% of women living in the United States are thought to suffer from dysmenorrhea, namely 10-15% of women experience dysmenorrhea. Dysmenorrhea affects women's activities, especially in female adolescents. Dysmenorrhea is a symptomatic phenomenon during menstruation including abdominal pain, cramps and lower back pain. The aim is to determine the relationship between stress levels and the incidence of dysmenorrhea pain in Midwifery students at Bandung Midwifery AcademyMethod: This type of research is analytical research with cross-sectional design, using the Chi-square test. The statistical test in this study uses the chi square test.Results: 26 (81.3%) respondents had normal menarche. 18 (56.3%) respondents had normal nutritional status. 21 (65.6%) respondents had moderate stress. There is a relationship between stress levels and the incidence of dysmenorrhea pain in Bandung Midwifery Academy students with a p-value of 0.001, and an OR value of 16.625, which means that stress can affect dysmenorrhea pain 16 times.Conclusion: There is a relationship between stress levels and the incidence of dysmenorrhea pain in students of Bandung Midwifery Academy. For further researchers, they can conduct research by adding other causal factors to be more effective in determining the factors that influence dysmenorrhea.